2020
DOI: 10.1155/2020/9835214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Fermentation of Sorghum on Resistant Starch Molecular Structure and Fermentation Property

Abstract: Relevant research results have suggested that fermentation can increase the content of sorghum amylose chains and their retrogradation value. Therefore, this study explored the effect of fermentation pretreatment on the yield, digestibility, molecular structure, and in vitro fermentation property of sorghum-resistant starch by conducting fermentation pretreatment of sorghum and extracting the resistant starch from fermented sorghum with pressure-heat compound enzyme method. The results were as follows. After f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…From Based on the above results, it can be inferred that, compared with NBS, the enzymes and organic acids produced by Lactobacillus plant-based dy-1 can debranch large-size amylose at the early stage of fermentation, reduce the average size of amylose, and increase the content of large-size amylose. Subsequently, due to the degradation of non-reducing outer ends of amylose and amylopectin, the content of small-size amylose increased, which was similar to the results of Ge et al 26 on fermented sorghum starch. However, with the advancement of fermentation, the smaller amylose and amylopectin were first degraded into oligosaccharides and oligosaccharides used by Lactiplantibacillus plantarum dy-1.…”
Section: Total Molecular Size Distribution Of Barley Starch Before An...supporting
confidence: 87%
“…From Based on the above results, it can be inferred that, compared with NBS, the enzymes and organic acids produced by Lactobacillus plant-based dy-1 can debranch large-size amylose at the early stage of fermentation, reduce the average size of amylose, and increase the content of large-size amylose. Subsequently, due to the degradation of non-reducing outer ends of amylose and amylopectin, the content of small-size amylose increased, which was similar to the results of Ge et al 26 on fermented sorghum starch. However, with the advancement of fermentation, the smaller amylose and amylopectin were first degraded into oligosaccharides and oligosaccharides used by Lactiplantibacillus plantarum dy-1.…”
Section: Total Molecular Size Distribution Of Barley Starch Before An...supporting
confidence: 87%
“…This result conforms with the study results of Opyd et al [39], who reported that high propionate content is related to high insoluble dietary fiber in apple seed and pomace. The production of butyrate content might be similar to the study of Ge et al [40], due to the fermentability of resistant starch in sorghum.…”
Section: ) Dietary Fiber Fermentabilitysupporting
confidence: 86%
“…Amylose and other substances produced by the fermentation degrade the starch molecules to a different degree, thereby weakening or damaging the amorphous region, that is, the non-crystalline region of starch granules, and entirely dissolving out the amylose also increasing the retrogradation value. Therefore, MOCAF amylose and the MOCAF RS content can significantly increase fermentation (12 hours), making it easier to produce resistant starch (Ge et al, 2020). The RS contents decreased with an increasing period of fermentation (12 to 24 hours), during which time amylase was leached from the granules, which increased the starch solubility and thereby increased its susceptibility to fermentation (Bavaneethan et al, 2015).…”
Section: Results Dan Discussionmentioning
confidence: 99%